Analisis Efektivitas Instalasi Pengolahan Air Limbah dan Penilaian Masyarakat Terhadap Pengolahan Limbah Cair Puskesmas Bonjeruk - Pariani, Lina; Sjah, Taslim; Sarjan, Muhammad (Lamda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2024)
Community Health Centers (Puskesmas) are health service facilities that produce wastewater containing microorganisms, toxic and radioactive chemicals that have a negative impact on the environment. This is because this waste has the potential to cause environmental and public health problems. The most dangerous health center waste is medical waste which is infectious in nature. Research conducted at the Bonjeruk community health center shows that efficiency is quite good. The WWTP uses activated sludge and has an efficiency level of more than 60% for all parameters and is classified as efficient. The highest level of efficiency is BOD parameters 56.5 mg/l to 5.83 mg/l (90%), COD 149 mg/l to 20.2 mg/l (86%), and TSS 22 mg/l to 5 .56 mg/l (75%), which means that waste water after going through the processing process does not contain pollutant levels above the threshold value (in accordance with the Liquid Waste Quality Standards for Hospital Activities) so it is suitable for discharge into public channels or water bodies. The public, especially visitors to the Bonjeruk Community Health Center, have a good perception of waste processing carried out by the Community Health Center.